2003
DOI: 10.1093/annonc/mdg117
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen alone versus adjuvant tamoxifen for operable breast cancer of the elderly: long-term results of the phase III randomized controlled multicenter GRETA trial

Abstract: The long-term results of the study confirm the 3-year interim analysis already reported. Surgery (radical or minimal) followed by adjuvant tamoxifen does not modify overall and breast cancer survival as compared with tamoxifen alone in early breast cancer of older women. Because of the high rate of local progressions with tamoxifen alone, minimal surgery followed by tamoxifen appears to be the appropriate treatment in such patients. More extensive surgery is not useful. Tamoxifen alone is an adequate alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(106 citation statements)
references
References 21 publications
5
98
0
3
Order By: Relevance
“…None of the studies evaluated the oestrogen receptor status of the women they recruited. Four eligible trials addressing surgery plus endocrine therapy vs primary endocrine therapy were identified, of which three have reported outcome data (Willsher et al, 1997;Capasso et al, 2000;Mustacchi et al, 2003;Fennessey et al, 2004), although there is currently no data from one in a form that can be meta-analysed (Capasso et al, 2000). Not all trials identified provided adequate information on all outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…None of the studies evaluated the oestrogen receptor status of the women they recruited. Four eligible trials addressing surgery plus endocrine therapy vs primary endocrine therapy were identified, of which three have reported outcome data (Willsher et al, 1997;Capasso et al, 2000;Mustacchi et al, 2003;Fennessey et al, 2004), although there is currently no data from one in a form that can be meta-analysed (Capasso et al, 2000). Not all trials identified provided adequate information on all outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of three trials was graded as A (Fentiman et al, 2003;Mustacchi et al, 2003;Fennessey et al, 2004) with the rest being graded as B (Gazet et al, 1994;Willsher et al, 1997;Kenny et al, 1998;Capasso et al, 2000). No potentially eligible study was excluded from the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tamoxifen as sole treatment) in older women. However, the five randomised controlled trials which have compared tamoxifen vs surgery have demonstrated better local control with surgery than with tamoxifen (Robertson et al, 1992;Gazet et al, 1994;Bates et al, 2001;Fentiman et al, 2003;Mustacchi et al, 2003). However, only one of these studies showed a reduction in survival with tamoxifen after 12 years of follow-up (Bates et al, 2001).…”
Section: Primary Endocrine Therapymentioning
confidence: 99%